2002
DOI: 10.1200/jco.20.5.1260
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Preventive Surgery and Screening for Breast and Ovarian Cancer in BRCA Mutation Carriers

Abstract: This study provides prospective evidence that genetic counseling and testing increased surveillance and led to risk-reducing operations, which resulted in diagnosis of early-stage tumors in patients with BRCA1 and BRCA2 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
168
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(183 citation statements)
references
References 33 publications
11
168
0
4
Order By: Relevance
“…Meijers-Heijboer et al 6 found that 50% of BRCA mutation carriers (4 of 8) who chose to undergo close surveillance rather than prophylactic mastectomy developed interval breast carcinoma; these interval malignancies were discovered 2-5 months after normal findings were noted on screening mammography. Similarly, Scheuer et al 11 reported that 6 of 12 patients (50%) developed interval breast carcinoma, which became evident 6 -10 months after normal findings were observed on screening mammography. These short periods between screening and the discovery of interval breast carcinoma suggest that annual mammography may be inadequate for screening BRCA mutation carriers.…”
Section: Discussionmentioning
confidence: 81%
“…Meijers-Heijboer et al 6 found that 50% of BRCA mutation carriers (4 of 8) who chose to undergo close surveillance rather than prophylactic mastectomy developed interval breast carcinoma; these interval malignancies were discovered 2-5 months after normal findings were noted on screening mammography. Similarly, Scheuer et al 11 reported that 6 of 12 patients (50%) developed interval breast carcinoma, which became evident 6 -10 months after normal findings were observed on screening mammography. These short periods between screening and the discovery of interval breast carcinoma suggest that annual mammography may be inadequate for screening BRCA mutation carriers.…”
Section: Discussionmentioning
confidence: 81%
“…Although efficacy of BPSO has been demonstrated (Rebbeck et al, 2005), the efficacy of gynaecological screening with (bi) annual transvaginal ultrasonography (TVU) and the serum tumour marker CA125 (Karlan et al, 1993;Burke et al, 1997) is still unclear. To summarize the literature on gynaecological screening of BRCA1/2 carriers, including overlap with the present study, eight interval cancers among 24 cancers were diagnosed among a total of 807 BRCA1/2 carriers (Table 1) (Laframboise et al, 2002;Liede et al, 2002;Scheuer et al, 2002;Fries et al, 2004;Kauff et al, 2005;Meeuwissen et al, 2005;Vasen et al, 2005;Gaarenstroom et al, 2006;Oei et al, 2006). Regretfully, most studies did not distinguish between prevalent and incident cases.…”
mentioning
confidence: 79%
“…Most of the studies concerning cancer screening after genetic testing for BRCA1/2 mutations report an increase in screening behavior, especially in carriers posttesting (Schwartz et al 2003;Lynch et al 2006;Foster et al 2007;Claes et al 2005b). In contrast to studies on HNPCC, the difference was not always significant (Scheuer et al 2002;Tinley et al 2004). Study conclusions on BRCA1/2 testing are not as clear and defined.…”
Section: Familial Breast Cancer (Brca1/2)mentioning
confidence: 91%
“…Study conclusions on BRCA1/2 testing are not as clear and defined. Behavior changes are not always statistically significant which may be explained by higher baseline compliance (Scheuer et al 2002). Interestingly, mutationnegative patients or patients with an inconclusive test result still showed adequate screening behavior and did not downshift or neglect their risk potential (Botkin et al 2003;van Dijk et al 2005).…”
Section: Familial Breast Cancer (Brca1/2)mentioning
confidence: 95%
See 1 more Smart Citation